Cellular Senescence and Tumor Suppression - Adams, Peter D.; Sedivy, John M.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Leonard Hayflick and colleagues coined the term "cellular senescence" to describe the inevitable and irreversible proliferation arrest of primary human cells in culture. Specifically, Hayflick and coworkers reported the phenomenon of replicative senescence in primary human fibroblasts, showing that these cells can proliferate in vitro for about 55 population doublings before their proliferative capacity succumbs to irreversible proliferation arrest. Since those original observations, major advances in our understanding have come in several areas. We now know that several other triggers, in addition to proliferative exhaustion, can trigger the senescence program. One important class of senescence triggers, and a focus of this volume, are activated oncogenes in primary untransformed cells. There is now good evidence to indicate that senescence in response to this cue is a potent tumor suppressor mechanism, through its ability to block proliferation of incipient cancer cells. However, senescence is not simply a passive proliferation arrest that impacts only the senescent cell itself, but rather, senescent cells influence their environment and neighboring cells through an active secretory program. This secretory program appears to facilitate senescence as a tumor suppression process. Cellular Senescence and Tumor Suppression collects a number of chapters from leaders in the field to review the molecular basis of senescence and its physiological functions, with a particular emphasis on the role of senescence in tumor suppression.
Senescence signals -- Telomere Biology and Biochemistry -- Role of RecQ Helicases in Nuclear DNA Repair and Telomere Maintenance -- Oncogene-Induced Senescence (OIS) as a Cellular Response to Oncogenic Stresses -- Stress-Induced Senescence -- The senescent phenotype -- The Secretome of Senescent Cells -- Chromatin Structure in Senescent Cells -- A Comparison of Senescence in Mouse and Human Cells -- The physiological consequences of senescence -- Replicative Senescence as an Intrinsic Tumor-Suppressor Mechanism -- Telomere Dysfunction and Senescence in Stem Cell and Tissues Aging -- Mining Cellular Senescence for Drug Targets.
Keywords: Medicine; Oncology; Human genetics; Toxicology; Biomedicine; Cancer Research; Human Genetics; Pharmacology/Toxicology.